2012
DOI: 10.2220/biomedres.33.1
|View full text |Cite
|
Sign up to set email alerts
|

The high-affinity choline transporter CHT1 is regulated by the ubiquitin ligase Nedd4-2

Abstract: The high-affinity choline transporter (CHT1), which is specifically expressed in cholinergic neurons, constitutes a rate-limiting step for acetylcholine synthesis. We have found that the exogenous ubiquitin ligase Nedd4-2 interacts with CHT1 expressed in HEK293 cells decreasing the amount of cell surface CHT1 by approximately 40%, and that small interfering RNA for endogenous Nedd4-2 enhances the choline uptake activity by CHT1 in HEK293 cells. These results indicate that Nedd4-2-mediated ubiquitination regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Consistent with our results, abolishment of ubiquitination for the glutamate transporter GLT1 required a total of 11 mutations, corresponding to all N - and C -terminus lysines. Similar findings were obtained for the choline transporter CHT1, which required 10 substitutions of the 12 intracellular lysine residues to reduce the levels of ubiquitination [ 13 , 43 ]. The classical example of redundancy is provided by the epidermal growth factor receptor (EGFR), where substitution of a minimum of six lysines in the kinase domain resulted in a dramatic decrease in the overall ubiquitination, but it was still not completely abolished [ 44 ].…”
Section: Discussionsupporting
confidence: 70%
“…Consistent with our results, abolishment of ubiquitination for the glutamate transporter GLT1 required a total of 11 mutations, corresponding to all N - and C -terminus lysines. Similar findings were obtained for the choline transporter CHT1, which required 10 substitutions of the 12 intracellular lysine residues to reduce the levels of ubiquitination [ 13 , 43 ]. The classical example of redundancy is provided by the epidermal growth factor receptor (EGFR), where substitution of a minimum of six lysines in the kinase domain resulted in a dramatic decrease in the overall ubiquitination, but it was still not completely abolished [ 44 ].…”
Section: Discussionsupporting
confidence: 70%
“…For example, brain deletion of Nedd4-2 leads to increased ENaC expression and hypertension induced by a high-salt diet that can be prevented by central infusion of the ENaC blocker benzamil7. However, Nedd4-2 can also regulate glutamate, dopamine and the CHT-1 choline transporters, and interacts with a number of neuronal NaV channels in cortical and dorsal root ganglia (DRG) neurons89101112. Recently, the identification of a Nedd4L missense mutation in a patient with epileptic encephalopathy and the isolation of missense mutations in highly conserved residues of Nedd4-2 in families with photosensitive generalized epilepsy has suggested that this E3 ligase, in addition to hypertension, is an epilepsy associated gene and can contribute to CNS pathologies13.…”
mentioning
confidence: 99%
“…To date, the role of ubiquitin and ubiquitination in the regulation of cholinergic function and CHT is largely unknown. A few recent studies suggest that CHT may be ubiquitinated[31] and ubiquitination may be involved in oxidative stress induced protein degradation of CHT[7]. Using TUBE pull-down assay, our study provides novel evidence that CHT undergoes poly-ubiquitination.…”
Section: Discussionmentioning
confidence: 73%